Comprehensive study of a long-lasting severe haze in Seoul megacity and its impacts on fine particulate matter and health. (April 2021) - Han, Seung-Beom; Song, Sang-Keun; Shon, Zang-Ho; Kang, Yoon-Hee; Bang, Jin-Hee; Oh, Inbo
Abstract: A long-lasting severe haze event was observed over the Seoul metropolitan region (SMR: Seoul, Incheon, and Gyeonggi-do), South Korea, in the winter of 2013 (January 12–16). We comprehensively investigated the atmospheric processes affecting particulate matter (PM) distributions during the haze event, as well as its impact on human health in the study area. These analyses were performed based on meteorological and PM observations and numerical modeling, which included the WRF-CMAQ modeling system and the Environmental Benefits Mapping and Analysis Program-Community Edition (BenMAP-CE). High PM10 concentrations during the haze event were mostly observed in the western and southern parts of the SMR. Significant differences (60–70 μg m −3 ) in the mean PM2.5 concentrations for haze and non-haze days were predicted mainly in the west-northwest areas of SMR. This might be primarily due to the pollutant transport (horizontal and vertical) from large emission sources (e.g., Chinese emissions) and, in part, their local accumulation (by local emissions) under high-pressure conditions and slow-moving air flows (i.e., blocking effect) around SMR. In addition, the enhanced PM2.5 concentrations in the study area during the haze event led to an increase in the number of premature deaths. Graphical abstract: Image 1 Highlgihts: A long-lasting haze event was analyzed using observations and modelling, WRF-CMAQ and BenMAP-CE. The haze event with high PM concentrations was primarily due to the pollutant transport from China. The increased PM concentrations were also partially due to local accumulation with meteorological conditions. Severe PM2.5 pollution on haze days led to an increase in the number of premature deaths.